Pemikiran HAMKA tentang Praktik Beragama Orang Minangkabau - Zikri, Adhiya Alfi; Zulqaiyyim, Zulqaiyyim (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
This article aims to explain the condition of religious practices in Minangkabau in the early 20thÂ century through the works of HAMKA. This study uses a historical method approach. Literature review is conducted to obtain primary and secondary sources. From the literature study, books by Haji Abdul Malik Karim Amrullah and other related writings related to the two figures related to the research theme were obtained. HAMKA criticized the practice of tarekat that did not conform to the teachings of the Quran and Hadith, as well as the traditional social system that was not in accordance with Islamic rules, such as in the case of inheritance and communal land. He also brought a new spirit in his preaching with a focus on the spirit of Islamic struggle and unity, as well as criticism of the rigidity of tradition and the importance of education to open up people's perspectives.